Survivor Tree - Colleen, Marcie; Becker, Aaron, 1974- (New York : Little, Brown and Company, 2021)
The Callery pear tree standing at the base of the World Trade Center is almost destroyed on September 11, but it is pulled from the rubble, coaxed back to life, and replanted as part of the 9/11 memorial.
Keywords: September 11 Terrorist Attacks, 2001 -- Juvenile fiction; Trees -- Juvenile fiction -- New York (State); Calley pear -- Juvenile fiction; Seasons -- Juvenile fiction; Memorials -- Juvenile fiction -- New York (State); September 11 Terrorist Attacks, 2001 -- Fiction; Trees -- Fiction -- New York (State); Calley pear -- Fiction; Seasons -- Fiction; Memorials -- Fiction -- New York (State); New York (N.Y.) -- Juvenile fiction; New York (N.Y.) -- Fiction; Picture books